Transgender people’s reasons for primary care visits: a cross-sectional study in France - Maud Garnier; Sarah Ollivier; Marie Flori; Christine Maynié-François (BMJ Open)
Objectives Our main objective was to describe transgender people’s reasons for consulting a general practitioner (GP) outside of transition-related issues; the secondary objective was to study the qualitative aspects of the primary care visits for this population.Design Descriptive, cross-sectional study in France.Setting The study questionnaire was distributed online and to healthcare centres in France.Participants Self-identified transgender people aged 18 and older.Primary and secondary outcomes Reasons for consulting were collected retrospectively and classified according to the International Classification of Primary Care, second edition (ICPC-2). The answers to the open-ended questions were analysed qualitatively by theme and occurrences.Results Out of 320 respondents, 50% visited their GP for a problem unrelated to their transition, with a total of 155 reported reasons. Procedures such as prescription renewal and administrative paperwork represented 33% of the reasons to visit, followed by general symptoms (15%). Benevolence from the physician was the most important criteria for a successful consultation.Conclusion Transgender people visit their GP for reasons either related (50%) or unrelated (50%) to transition. When unrelated, reasons appear to be similar to the reasons found in the general population. Further research and training should be developed on comprehensive primary healthcare for transgender people to provide quality patient-centred care for transgender patients.